2021
DOI: 10.1111/jssr.12750
|View full text |Cite
|
Sign up to set email alerts
|

Religious Fundamentalism and Quest as Predictors of Moral Foundations Among Iranian Muslims

Abstract: Does religion make us moral? How do individual differences in religious beliefs influence morality? Can we predict differences in moral concerns by certain facets of religiousness? Here, we attempted to answer these hotly debated questions within a novel psychological framework called "moral foundations theory." We extended past research on the relationship between moral foundations and religiosity that was limited to Christian samples in WEIRD (Western, Educated, Industrialized, Rich, and Democratic) societi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 51 publications
(56 reference statements)
0
2
0
Order By: Relevance
“…Moral Foundations Questionnaire (MFQ). To measure the endorsement of the five moral foundations, all participants completed the Farsi version of the 30-item moral foundations questionnaire (MFQ; Graham et al, 2011) validated by Nejat and Hatami (2019) and recently used in psychological studies in Iran (see Atari, Graham, et al, 2020;Atari, Lai, et al, 2020;Baboli & Karimi-Malekabadi, 2020;Mikani & Rasoolzadeh Tabatabaei, 2021). Caring for others or avoiding harm (Harm/ Care; for example, compassion for those who are suffering is the most crucial virtue), fairness and justice (Fairness/Reciprocity; for example, when the government makes laws, the number one principle should be ensuring that everyone is treated fairly), loyalty to one's group (Ingroup/Loyalty; for example, I am proud of my country's history), obedience to authority (Authority/Respect; for example, respect for authority is something all children need to learn), and maintaining bodily and spiritual purity (Purity/Sanctity; for example, people should not do things that are disgusting, even if no one is harmed).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moral Foundations Questionnaire (MFQ). To measure the endorsement of the five moral foundations, all participants completed the Farsi version of the 30-item moral foundations questionnaire (MFQ; Graham et al, 2011) validated by Nejat and Hatami (2019) and recently used in psychological studies in Iran (see Atari, Graham, et al, 2020;Atari, Lai, et al, 2020;Baboli & Karimi-Malekabadi, 2020;Mikani & Rasoolzadeh Tabatabaei, 2021). Caring for others or avoiding harm (Harm/ Care; for example, compassion for those who are suffering is the most crucial virtue), fairness and justice (Fairness/Reciprocity; for example, when the government makes laws, the number one principle should be ensuring that everyone is treated fairly), loyalty to one's group (Ingroup/Loyalty; for example, I am proud of my country's history), obedience to authority (Authority/Respect; for example, respect for authority is something all children need to learn), and maintaining bodily and spiritual purity (Purity/Sanctity; for example, people should not do things that are disgusting, even if no one is harmed).…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Atari, Graham, et al (2020) explored the moral domains in Iran and proposed "Qeirat" as a culture-specific moral foundation. More recently, Mikani and Rasoolzadeh Tabatabaei (2021) showed that after controlling for general religiosity as well as other religious dimensions, religious fundamentalism, and intrinsic religiosity are predictors of binding foundations, and quest religiousness predicts individualizing foundations in Iran.…”
Section: Introductionmentioning
confidence: 99%
“…They were endowed with characteristics and personalities that could serve as models for the people. While these attributes were primarily portrayed in terms of morals, ethics, behavior, and leadership (Ali, 2009;Harmaini et al, 2022;Mikani & Rasoolzadeh Tabatabaei, 2021), their language had not been explicitly explored.…”
mentioning
confidence: 99%